2021
DOI: 10.5847/wjem.j.1920-8642.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

What is the ideal approach for emergent pericardiocentesis using point-of-care ultrasound guidance?

Abstract: BACKGROUND: Traditionally performed using a subxiphoid approach, the increasing use of pointof-care ultrasound in the emergency department has made other approaches (parasternal and apical) for pericardiocentesis viable. The aim of this study is to identify the ideal approach for emergency-physicianperformed ultrasound-guided pericardiocentesis as determined by ultrasound image quality, distance from surface to pericardial fl uid, and likely obstructions or complications. METHODS:A retrospective review of poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…When choosing the site of the emergency pericardiocentesis, the ideal approach for using point-of-care ultrasound guidance should take into consideration the distance of effusion to the probe, image quality, and predicted complications. Stolz et al predicted that the subcostal approach had the highest complication rate compare to other methods [ 12 ]. This was because of its long distance from the skin to the pericardial space, which increased the risk of injury to the liver, blood vessels and bowels.…”
Section: Discussionmentioning
confidence: 99%
“…When choosing the site of the emergency pericardiocentesis, the ideal approach for using point-of-care ultrasound guidance should take into consideration the distance of effusion to the probe, image quality, and predicted complications. Stolz et al predicted that the subcostal approach had the highest complication rate compare to other methods [ 12 ]. This was because of its long distance from the skin to the pericardial space, which increased the risk of injury to the liver, blood vessels and bowels.…”
Section: Discussionmentioning
confidence: 99%
“…The subxiphoid approach has the longest distance from the skin to the pericardial fluid. 8 In contrast, the increasing use of the TTE has enabled the other 2 methods to be safer than the subxiphoid approach. In fact, previous studies have suggested that the parasternal approach is safest if guided by a TTE.…”
Section: Discussionmentioning
confidence: 99%
“…This was treated with full anticoagulation with low-molecular-weight heparin. To perform her pericardiocentesis, three possible methods were considered; (1) subcostal approach had overlying liver and abdominal adiposity rendering this conventional access inadvisable, published series indicate an up to 20% complications rate which is also the most indirect route and in current practice it accounts for the bulk of adverse events1 2; (2) apical approach was hindered by breast, chest adiposity and overlying lung with the potential of causing pneumothorax and finally; (3) parasternal approach which is increasingly done in the emergency department by non-cardiologists and was favourable 3. Her echocardiogram (figure 1A) revealed significant effusion around the heart with tamponade physiology on doppler and evidence of diastolic right ventricular collapse.…”
Section: Descriptionmentioning
confidence: 99%